Морфологические различия между костями черепа карасей - круглого (золотого) и серебряного - Куровский, Е.А. (Вестник зоологии, 1968)
Studying the cranial bones of Carassius carassius L. and Carassius auratus gibelio Bloch considerable differences were found between these bones both as to the relative dimensions and as to their general configuration. The differences revealed can serve as a basis when differentiating the crucian skeletons from the paleontologic material and subfossil remains.